Antibacterial activity of endophytic fubgi isolated from Dangkalan Calophyllum inophyllum (Linn.). - Clarito, Sheena Grace A. (2014.)
Studies on endophytic fungi isolated from medicinal plants receive increasing interest worlwide due to the potential of endophytes as sources of novel metabolites with high therapeutic value. These could be used to replace synthetic drugs in the market that has high toxicity and adverse side effects, and to combat reemerging diseases due to antibiotic resistance. Thus, this study was conducted to screen the leaves of Calophyllum inophyllum, a medicinal tree, for its associated endophytic fungi and to test their potential antibacterial activity. Specifically, it aimed to 1) identify and determine colonization frequencies of endophytic fungi found in the leaves of C. inophyllum, and 2) determine antibactrial activity of fungal isolates against Gram positive bactria (Staphylococcus aureus and Bacillus subtilis) and Gram negative bacteria (Escherichia coli and Salmonella sp.). Leaf samples collected in Brgy. Dancalan, Antique, Philippines were bored into leaf discs, surface sterilized, placed onto PDA plates, and incubated at 25 +- 2 degrees centigrade for 1-2 weeks. Plates were examined daily for emerging distinct fungal colonies, which were isolated, purified by repeated re-isolation, and identified using standard taxonomic keys. Crude methanolic extracts of dominant species were obtained by solid phase extraction and were tested for antibacterial acivity using disc diffusion method. A total of nine species were identified, mostly belonging to Deuteromycetes, Sclerotium sp. was the most dominant species in C. inophyllum leaves having 70 percent frequency of occurrence followed by Aspergillus flavus (11.8 percent). Aspergillus sp. (9.1 percent) Aspergillus niger (4.5 percent) and Geotrichum candidum (1.8 percent). Among the extracts, only G. candidum exhibited signifiant activity against S. aureus and Salmonella sp. showing broad spectrum antibacterial activity. Thus, the study shows that C. inophyllum harbors few endophytic fungi that can be potential sources of antibiotics.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Dangkalan; Calophyllum inophyllum (Linn.)